Dendritic Cells Are Associated with Prognosis and Survival in Breast Cancer - Joanna Szpor; Joanna Streb; Anna Glajcar; Paulina Frączek; Aleksandra Winiarska; Katarzyna E. Tyrak; Paweł Basta; Krzysztof Okoń; Robert Jach; Diana Hodorowicz-Zaniewska (Diagnostics, 2021)
Dendritic cells (DCs) constitute a part of the tumour microenvironment, but we are still far from understanding their complex role in immune response to the tumour. This study aimed to investigate the density of DCs expressing CD1a, CD83, CD123, DC-LAMP3 (CD208) and DC-SIGN (CD209) in breast cancer. The correlations between DC density and molecular subtype of breast cancer, its hormone receptor status, spatial location and their associations with clinical and pathological prognostic factors were evaluated. We have shown that intratumoural CD1a+ cells were significantly associated with progression-free survival. For LAMP3+ and CD123+ DCs, higher cell densities were associated with non-luminal as compared to luminal cancer phenotype. In contrast, dense CD83+ DC infiltrate was observed in luminal tumours. The number of CD1a+ DCs in both locations was the highest in luminal B/HER2+ cancers. The highest positive cell count of LAMP3+ cells was observed in the triple-negative subtype in both locations. We found higher numbers of LAMP3+ DCs both intratumourally and at the invasive margin, as well as CD123+ DCs intratumourally in tumours with negative expression of oestrogen or progesterone receptors. Our study demonstrates associations between DC subpopulations and histological and clinical characteristics, as well as molecular subtypes in breast carcinoma.